Phase-transition time of a commercial magnetron driving a surface-wave plasma load. (1st February 2023) - Kim, Dohan; Cha, Ju-Hong; Shon, Chae-Hwa; Kim, Jong-Soo; Han, Seong-Tae
Abstract: Surface-wave plasma which generates a specific wave mode between the plasma and a dielectric window by microwave is superior to RF plasmas in producing relatively higher electron density at low temperature. To challenge the uniformity issue of the microwave plasma whose wavelength is shorter than the size of the industrial system, rotating field systems by imparting a phase difference of microwaves from multiple inputs over time are attracting attention. The authors investigate the feasibility of a phase-locked-loop (PLL) injected magnetron (MGT) as a highly efficient microwave source to modulate the phase difference of high-power microwaves fast and precisely. The phase-transition time of the MGT with a plasma load is estimated to be below 45 ns by theoretical analysis and experimental measurement. The results show that the phase-modulation frequency of microwaves with the PLL-injected MGT is capable of reaching up to 10 MHz.